Temperature stress effects in Quercus suber leaf metabolism. - Chaves, Inês; Passarinho, José António P; Capitão, Cláudio; Chaves, Maria Manuela; Fevereiro, Pedro; Ricardo, Cândido P P (Journal of plant physiology, 2011)
Based on projections that climate changes are will intensify in the near future, it is important to understand how plants respond to climate. Consequently, we have been studying the effect of contrasting temperatures on leaf metabolism of Quercus suber, an important Mediterranean oak. Potted plants were grown under controlled conditions for 53 days at 28°C or 10°C. The accumulation of major soluble metabolites was analyzed by NMR. The relative levels of transcripts of genes encoding key enzymes of the shikimate and phenylpropanoid pathway (CS, PAL, CAD and ChS) were examined by means of quantitative, real-time RT-PCR. At 10°C, in the pre-existing leaves, the concentrations of sucrose, quercitol and catechin were higher, as were PAL and ChS transcripts. At 28°C, however, it was the concentration of quinic acid that was higher, as were the concentrations of CS and CAD transcripts. We conclude that contrasting temperatures greatly influence Q. suber metabolism and that a deeper analysis of the effects of more extreme temperatures is needed to understand the possible effects of temperature changes on Q. suber metabolism and physiology.
Keywords: Abiotic stress response; Cork oak; Phenol metabolism; Secondary metabolism